Strong reflexivity / weak theory - Τσέκερης Χαράλαμπος (The Greek Review of Social Research, 2012)
The methodological conception of reflexivity is often associated to qualitative research, multi-level meta-theoretical analyses and, in general, epistemological questions and answers. However, common («strong») reflexive thinking about knowledge and culture tends to arrogantly exclude alternative theorizations and to implicitly ignore the irreducibility of the «ethical dimension». The «reinvention» of this crucial dimension, within contemporary sociology and critical research, entails the substantial incorporation of the «weak» performative circular reasoning (Maturana/Varela, Luhmann), as well as a new reflexive ethos and aesthetic of epistemic humility. The issue here is indeed the fruitful pluralist maximization of both ethical and cognitive possibilities. In this respect, the innovative «it could be otherwise» clause of radical intellectual inquiry remains central to our theoretical world and self-accounts.